ضوابط ضَرْبِ الطلبة في الحلقات القرآنيّة: دراسة استقرائية وصفية: Regulations of hitting students in Quran memorization circles: An inductive and descriptive study - Abdulbari Almehdar, Abdulaziz Mustafa; Jibo, Salihu Mus (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث هدفت هذه الدراسة إلى تحديد الضوابط والشروط التي تُراعى عند ضرب الطلاب في حلقات تحفيظ القرآن، وذلك لحلِّ الإشكاليَّة المُثارة في المجال التربوي حول مسألة الضرب، ولبيان صلاحيته للتأديب في حلقات التحفيظ، وهذا سبب كتابة هذا البحث، قال رسول صلّى الله عليه وسلّم: "عَلِّمُوا أَوْلادَكُمُ الصَّلاةَ إِذَا بَلَغَوا سَبْعًا وَاضْرِبُوهُمْ عَلَيْهَا إِذَا بَلَغَوا عَشْرًا..." (Al bazzar 1992) ولقد اتّبعت المنهج الاستقرائي الوصفي، ولقد قمتُ بمناقشة مسألة الضرب وذكرت الأطراف فيها ثمّ بيّنت الراجح فيها، وقد توصلت الدراسة إلى أنّ الضرب وسيلة شرعيّة ثابتة للتأديب؛ لكن بضوابطها، ثم إنّي بعد استقراء هذ الضوابط وجمعها لاحظتُ أنّ منها ما يكون قبل الضرب كعمر الطالب المراد ضربه، ومنها ما يكون في أثنائه كمقدار الضرب، ومنها ما يكون بعده كعدم الاستهزاء بالطالب أو السماح به، فعلى ذلك قَسَّمت هذه الضوابط في الدراسة، ، كما توصّلت الدراسة إلى أنّ النبي صلّى الله عليه وسلّم شرع هذه الوسيلة قولاً إلّا أنّه لم يستخدمها فعلاً. ABSTRACT This study aimed to identify the regulations and conditions to be observed when striking students in Qur'an memorization circles (Halaqah), in order to resolve the issue raised in the educational field regarding the matter of hitting, and to clarify its validity as a means of discipline in memorization circles. This is the reason for writing this research. The Messenger (peace and blessings be upon him) said: “Command your children to pray when they are seven years old, and strike them over it when they are ten...” (Al-Bazzar, 1992). I followed the descriptive inductive methodology. I discussed the issue of hitting, mentioned the differing views on it, and then clarified the more correct opinion. The study concluded that hitting is a legitimate and established means of discipline — but only within its conditions. After surveying and collecting these conditions, I observed that some of them relate to the stage before hitting, such as the age of the student to be hit; some during, such as the extent of the hitting; and some after, such as refraining from mocking the student or permitting others to do so. Accordingly, I categorized these conditions in the study, The study also concluded that the Prophet (peace and blessings be upon him) legislated this method in speech, but did not apply it in practice.